(untitled) (The Peerian Journal, 2023)
It has been described the CRISPR-Cas9 system ,the most exciting achievement in biomedical research since the dawn of genetic engineering in the 1970s, with the broad scope to better understand and treat human and animal diseases and its potential to revolutionize medical and agricultural research by identifying the double helix of DNA and the role it in the genetic formation of living organisms. The CRISPR tool is a giant step forward in this regard, and compared to existing research tools, it is a fast, easy, reliable, and relatively low-cost way to target and refine specific genetic sequences. Therefore, this paper discussed the importance of this technology, the way genes work in cells, and the most effective new medical treatments for a group disease that destroys the living body